Practice of quality control circle activities in improving the standardized implementation rate of peripheral venous thrombolysis for lower-limb deep venous thrombosis (提高下肢深静脉血栓形成患者外周静脉溶栓执行规范率的品管圈实践) - BAI Mei (白枚); LI Yaya (李娅娅); YAN Yan (闫燕); LIU Mingming (刘明明); LI Yin (黎殷); XU Yuanle (许远乐) (Journal of International Translational Medicine Limited, 2023)
Objective To investigate the effect of quality control circle (QCC)activities in improving the standardized implementation rate of peripheral venous thrombolysis for lower-limb deep venous thrombosis (DVT). Methods A QCC group was set up. Factors causing failed implementation rate of DVT were analyzed, and countermeasures were carried out for continuous quality improvement. Results The standardized implementation rate of peripheral venous thrombolysis for lower-limb DVT increased form 33. 33% before QCC activities to 91. 25% after QCC activities, with a significant difference (P＜0. 05). Conclusion The implementation of QCC activities for continuous quality improvement of standardized procedure of peripheral venous thrombolysis may help to improve the effect of thrombolytic therapy. (目的 探讨品管圈在提高下肢深静脉血栓形成(DVT)患者外周静脉溶栓执行规范率中的效果。方法 成立品管圈小组, 进行品管圈知识培训, 选定活动主题, 进行现状调查, 分析下肢DVT患者外周静脉溶栓执行不合格原因, 制定对策并实施质量持续改进。结果 下肢DVT患者外周静脉溶栓执行规范率由品管圈活动前的33. 33%提高至开展品管圈活动后的91. 25%, 差异有统计学意义(P＜0. 05)。结论 开展品管圈活动, 对下肢DVT患者外周静脉溶栓执行规范率进行持续改进, 可以有效提高溶栓效果。)